Bangladesh: Systematic analysis of domestic production and world market shocks - Mukashov, Askar; Jones, Eleanor; Thurlow, James (International Food Policy Research Institute, 2024)
This study explores Bangladesh’s vulnerability to economic shocks and identifies those contributing most to eco-nomic uncertainty. The Bangladesh Computable General Equilibrium (CGE) model was employed to simulate a range of potential economic outcomes under various shock scenarios sampled using historical data to capture domestic agricultural yield volatilities and world market price uncertainty for traded goods. Data mining and machine learning methods were applied to quantify the contribution of each shock to the uncertainty of economic outcomes (gross domestic product [GDP], private consumption, poverty, and undernourishment). Our findings suggest that potential variation in Bangladesh’s GDP ranges from +0.8 to -1.0 percent to baseline, with domestic shocks ac-counting for 53.7 percent of uncertainty, and remaining 41.7 percent are explained by the volatility of world market prices and Foreign Exchange (FX) flows. At the same time, private consumption is more uncertain (from +4.0 to -3.5 percent to base), and external factors are the most important risk contributors (70.1 percent is world prices and 2.9 percent is FX flows). Similarly, external factors contribute roughly two-thirds to the potential variation of national poverty and undernourishment rates that fluctuate from -2.4 to +1.8 and –2.2 to +1.9 relative to the baseline rates percentage points respectively. Understanding how potential shocks might impact various segments of the Bang-ladesh economy and population is a critical first step in facilitating a discussion on risk mitigation strategies that include increasing sectoral productivity or diversifying production to reduce reliance on high-risk sectors.